O Culminar de um Sonho de Criança - Pedro Alexandre Morais Alves (2022)
The professional internship is part of the 2nd year of the Master's Degree in Teaching Physical Education in Primary and Secondary Education of the Faculty of Sport, University of Porto. The aim of the internship is to promote to the trainee students a first contact with what their future profession will be. The professional internship is guided by a Guidance Teacher and a Cooperating Teacher of the school where it is carried out. This document addresses the evolutionary process of the trainee teacher, his/her training and learning process. It is divided into five chapters: the introduction, which describes the purpose of the document. The second chapter includes the personal framework, i.e., the initial expectations in relation to the internship, the personal characterization, what led me to choose this course and all the experiences and sports experiences. In the next chapter, the framework of professional practice refers to the components of professional training: institutional, legal and functional. In chapter four are inserted the three areas that include information about the preparation, implementation and evaluation of the teaching learning process, as well as the activities developed by the internship core. The last area integrates an action research study, where through a questionnaire we tried to find out if the school fits the definition of an active school. The last chapter, conclusions and prospects for the future, contains a final reflection on the probationary year and prospects for the professional and personal future. In short, this report describes all the experiences that took place during the year, which allowed to prepare, to develop knowledge, to learn new skills that will be fundamental for the professional future of Physical Education teacher.